A Depot Medroxyprogesterone Acetate Dose That Models Human Use and Its Effect on Vaginal SHIV Acquisition Risk. (1st August 2016) - Butler, Katherine; Ritter, Jana M.; Ellis, Shanon; Morris, Monica R.; Hanson, Debra L.; McNicholl, Janet M.; Kersh, Ellen N.
Abstract : Introduction: Hormonal contraception with depot medroxyprogesterone acetate (DMPA) may increase HIV acquisition risk, but observational human studies are inconclusive, and animal models can help investigate this risk. In this study, we test the impact of a low DMPA dose, designed to resemble human contraceptive use, on Simian-Human Immunodeficiency Virus (SHIV) acquisition risk in pigtail macaques ( Macaca nemestrina ). Methods: Macaques metabolize DMPA faster than humans. We previously identified a per-weight DMPA dose and administration frequency that achieves long-lasting suppression of ovulation in macaques. Eight macaques were given 1.5-mg/kg DMPA monthly, whereas 11 were untreated controls. For comparison, women receive 150 mg (approximately 2 mg/kg) every 3 months. We exposed monkeys to 20 suboptimal SHIV challenges, designed to slowly infect half of controls and allow increased infection in the DMPA group. Results: It took a median 5.5 viral challenges to infect DMPA-treated macaques and 9 challenges for controls ( P = 0.27; exact conditional logistic regression). The exact odds ratio was 2.2 (CI: 0.6 to 8.3). Ovulation was suppressed, and the vaginal epithelium was thinned after DMPA treatment in all animals (mean, 30 and 219 mm in DMPA-treated and control macaques, respectively, P = 0.03, t test using the Satterthwaite degrees-of-freedom approximation). Conclusions: SHIV infections in DMPA-treated macaques were 2.2 times those of controls, but this was not statistically significant. The result is remarkably similar to studies of human DMPA use, which have shown HIV risk increases of a similar magnitude and of variable significance. Taken together with previous studies of higher DMPA doses in macaques, the results suggest a dose-dependent effect of DMPA on Simian Immunodeficiency Virus (SIV) or SHIV acquisition. Abstract : Supplemental Digital Content is Available in the Text.